REFLECTING ON THE POLYCODE TEXT THEORY THROUGH THE CONCEPTS OF POETIC DWELLING IN MARTIN HEIDEGGER’S THOUGHT (Philological Studies, 2022)
This text is an attempt to apply the theory of the polycode text to the thinking of the later Heidegger with a focus on his reflection on the phenomena of building and dwelling. The main point of departure will be his text "Building Dwelling Thinking", which has had a great impact on both architectural theory and practice, as well as on contemporary art and design theory. This will be considered in the context of Heidegger's reflection on the phenomenon of language.